Creative Freedom and Holistic Growth: Implementation of the STEAM Approach in Islamic Early Childhood Education - Nadlifah; Latif, Muhammad Abdul (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
The rapid evolution of technology continues to drive the demand for highly skilled human resources capable of competing in an increasingly dynamic global environment. Preparing superior human resources from an early age is crucial to meeting these demands. This study investigates how the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach is implemented and its impact on early childhood education at RA Fun Islamic School in Indonesia. Employing a qualitative case study methodology, data were gathered through observations, semi-structured interviews with educators, parents, and administrators, as well as an analysis of relevant documentation. The findings highlight STEAM's focus on nurturing creative freedom, critical thinking, and collaboration among young learners. Children participating in activities such as building structures and integrating arts with mathematics showed notable outcomes, including independent problem-solving and the development of unique solutions. The study also emphasizes the role of introducing simple engineering concepts and integrating technology to create dynamic and engaging learning environments. Despite these benefits, challenges like limited resources and the need for teacher training were identified. This research underscores the transformative potential of STEAM in promoting cognitive and social growth in early childhood education. Future studies should explore how this approach can be scaled to diverse educational settings and evaluate its long-term effects.